Science Bulletin - An, Rui.; Chen, Xiao-Ya.; SpringerLink (Online service) (Beijing : Science China Press : Imprint: Science China Press, co-published with Springer.)
Chinese Science Bulletin is a comprehensive academic journal cosponsored by the Chinese Academy of Sciences and the National Natural Science Foundation of China. Its primary mission is to encourage communication of the novel and important research results in various fields of natural sciences. The contributions are required to be readable and have immediate and far-reaching implications to a broader audience. Chinese Science Bulletin is cited in CA, EI, JICST, and some products of ISI, including Science Citation Index (SCI-CDE), SCI Search, Current Contents (PC&E), and Research Alert. Chinese Science Bulletin is published twice monthly by Science China Press. Contributions published in Chinese Science Bulletin News & Views: Introduce and comment on the research highlights published in Chinese Science Bulletin and other international journals and outstanding work awarded the national prizes (1800 words). Progress: Introduce and comment on the substantial advance and its importance in the fast-developing areas (3600 words). Review: Summarize the representative progress in core scientific disciplines, comment on the research status, and make suggestions for the future work (10,000 words, with a 600-word abstract). Frontiers: Comment on excitement and existing problems of core fields, and offer suggestions for the future research. The contributions are usually solicited by editor$1 (Bs invitation. Articles: Originally report the innovative and valuable findings in natural sciences (9000 words, with a 300-word abstract). Brief Communication: Briefly report the novel and innovative findings in natural sciences (1800 words). The accepted contributions will be scheduled for publication within one month. Forum: Comment on the important academic issues, administration policies and state scientific programmes, and give views about the theoretical problems such as the relation between scientific development and social evolution (6000 words, with a 200-word abstract). Correspondence: Discuss and make reply to the contributions published in Chinese Science Bulletin, or introduce and comment on a controversial issue of general interest (4000 words). Trend: Report weighty scientific news, information, and academic affairs, as well as the significant international conferences held in China (800 words). Books: Introduce and comment on quality monographs of natural sciences (800 words).s
Keywords: Science; Chemistry; Earth sciences; Life sciences; Physics; Engineering; Science, Humanities and Social Sciences, multidisciplinary; Life Sciences, general; Physics, general; Chemistry/Food Science, general; Earth Sciences, general; Engineering, general